Fabrication of 90° wall of {100} plane on (100) Si by NaOH solution via design of experiments - Chupong Pakpum (2018)
The experimental trials were conducted by design of experiments (DOE) technique to find an anisotropic wet etching condition that achieves 90° wall angle on silicon (100) orientation wafer. Three considered factors assigned to the DOE were NaOH concentration, solution temperature, and stirring speed. The response aimed for this study was not only targeting at 90° wall but also providing highest etch rate. The experimental results showed that in order to fabricate the 90° wall angle, the best etching condition using was 30% wt NaOH concentration, 80°C solution temperature, and 300 rpm stirring speed. This condition gave an etch rate of 1245 nm/min with surface roughness (R a ) of 701.48 nm. © (2014) Trans Tech Publications, Switzerland.